1995
DOI: 10.1016/0094-730x(94)00022-l
|View full text |Cite
|
Sign up to set email alerts
|

Speech-motor and linguistic skills of young stutterers prior to onset

Abstract: Theorists have increasingly suggested that both speech-motor and linguistic factors are involved in the etiology of stuttering. This contention has been supported by findings that tend to indicate that youngsters who stutter have a slower speech rate and are less linguistically skilled than nonstutterers. However, no inferences can be drawn from these findings as to the nature or the causation of this disorder. This is because the aforementioned findings might be a result rather than a cause of the disorder. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 26 publications
1
13
0
3
Order By: Relevance
“…The male-to-female ratio of the 40 genotyped individuals who have ever stuttered is 1.5:1, which is consistent with some previous estimates of the sex ratio close to onset (1.6:1 in Kloth, Janssen, Kraaimaat, & Brutten, 1995;1.65:1 in Mansson, 2000), although lower than others (2.1:1 in Yairi & Ambrose, 2005), and considerably lower than the 3 or 4 to 1 reported for adults (Bloodstein, 1995).…”
Section: Study Populationsupporting
confidence: 80%
“…The male-to-female ratio of the 40 genotyped individuals who have ever stuttered is 1.5:1, which is consistent with some previous estimates of the sex ratio close to onset (1.6:1 in Kloth, Janssen, Kraaimaat, & Brutten, 1995;1.65:1 in Mansson, 2000), although lower than others (2.1:1 in Yairi & Ambrose, 2005), and considerably lower than the 3 or 4 to 1 reported for adults (Bloodstein, 1995).…”
Section: Study Populationsupporting
confidence: 80%
“…The task force concluded that the role of these risk factors in screening was unclear and that a list of risk factors had not been developed or tested for selective screening for speech and language delay. 7 Only 4 [8][9][10][11] of the 16 studies reviewed by the USPSTF 7 considered risk factors in children who were Յ24 months of age. Of these 4, 1 focused solely on stuttering, 9 and the remaining 3 differed markedly in the speech and language domains studied and in the derivation and composition of the samples.…”
mentioning
confidence: 99%
“…7 Only 4 [8][9][10][11] of the 16 studies reviewed by the USPSTF 7 considered risk factors in children who were Յ24 months of age. Of these 4, 1 focused solely on stuttering, 9 and the remaining 3 differed markedly in the speech and language domains studied and in the derivation and composition of the samples. Surprisingly, none investigated the contribution of gender, SES, birth order, perinatal factors, or parental education.…”
mentioning
confidence: 99%
“…Both their pediatrician and their parents reported them to have normal intelligence and to be normally developing children. All of the participating children had demonstrated that they functioned within age-related normal range for receptive and expressive language (Kloth et al, 1995). And, each of the participating children passed a pure-tone audio metrie hearing screening test.…”
Section: Subjectsmentioning
confidence: 99%